KEMAMPUAN DAYA TAHAN ATLET BOLA TANGAN KOTA SURABAYA MENGGUNAKAN BRONCO - Habain Sila Perdana; Ristanti Puji Astuti; Miftahudin Miftahudin (Journal of Physical Activity and Sports (JPAS), 2026)
This study aims to describe the physical endurance levels of male handball athletes in Surabaya. Handball is a high-intensity sport played for minutes, requiring optimal fitness to maintain athlete performance throughout the match. Optimal physical condition is key for athletes to perform physical activities without excessive fatigue. The research method used was descriptive quantitative. The study subjects consisted of 21 male handball athletes from Surabaya. Data collection was conducted through tests and direct measurements on the field to obtain factual data regarding the athletes' cardiorespiratory endurance capacity. The results showed that the highest athlete achievement score was 93.83, while the lowest score was 76.79. Based on the data analysis, none of the athletes achieved the standard benchmark of 55.00 ml/kg/min. Overall, the average physical performance of the sample was below 100% of the established standard. Based on these results, it can be concluded that the physical endurance level of male handball athletes in Surabaya is considered poor. These results are expected to serve as evaluation material for coaches to improve the intensity and quality of future physical training programs